ANALYSIS OF COMMUNITY COMPLIANCE DURING THE COVID-19 PANDEMIC - Toding, Audy Christania; Suryaningsi, Suryaningsi (Unmul Civic Education Journal, 2022)
COVID-19 is a virus that has existed since 2019 originating from Wuhan, China. It has been in Indonesia since 2020, precisely in March which was announced by the president, Joko Widodo. This virus is a zoonosis that is transmitted between animals and humans. Many efforts have been made by the government to minimize the transmission of COVID-19. However, this will not happen if there is a lack of attention from the community itself in implementing the health protocols that have been made by the government. The purpose of this study was to analyze public compliance with health protocols during this pandemic. This research method uses qualitative methods. The results show that there are still people who are not aware of the importance of health protocols and lack understanding of current conditions, health workers continue to provide education to the public to always comply with health protocols as well as RT heads who always faithfully give directions to their citizens to always comply with the protocol. existing health. So the importance of public awareness in dealing with the COVID-19 virus so that you and others stay healthy.